Reveal the pharmacodynamic substances and mechanism of an edible medicinal plant Rhodiola crenulate in DSS-induced colitis through plasma pharmacochemistry and metabolomics - Yu Peng; Xiaoao Xiao; Tingting Ji; Xinyuan Wang; Yixuan Xu; Jianbo Xiao; Hui Cao; Zhiyong Chen; Huifan Liu; Yuanqing Gao; Hongxun Tao (Food Science and Human Wellness)
Rhodiola crenulate is the edible medicinal herbal medicine widely used for altitude sickness in China. Interestingly, our previous work has found that R. crenulate extract (RCE) could significantly improve the pathology associated with dextran sulfate sodium-induced colitis. Thus, the current research aims to reveal the pharmacodynamic material basis of RCE, as well as its mechanism against colitis. The chemical characterization of RCE was performed by UHPLC-HR-MS, through which a total of 88 constituents were identified. Meanwhile, our results also found 29 constituents absorbed into blood and 8 metabolized absorbable compounds. The decreased flavonoids prototype and the elevated sulfated products of phenols were observed under pathophysiological conditions of colitis. The metabolomics study revealed that colitis caused the alternation of fatty acid metabolism, steroid hormone biosynthesis and bile acid metabolism. Correspondingly, RCE could prevent colitis by improving fatty acid metabolism and secondary bile acid metabolism.